Induction of Resistance Mediated by an Attenuated Strain of Valsa mali var. mali Using Pathogen-Apple Callus Interaction System - Qingming Zhang; Caixia Wang; Daojing Yong; Guifang Li; Xiangli Dong; Baohua Li (The Scientific World Journal)
To study the induced resistance in apple against Valsa mali var. mali (Vmm), a Vmm–apple callus interaction system was developed to evaluate the induced resistance of an attenuated Vmm strain LXS081501 against further infection by a virulent Vmm strain LXS080601. The infection index was up to 97.32 for apple calli inoculated with LXS080601 alone at 15 days after inoculation whereas it was only 41.84 for calli pretreated with LXS081501 followed by LXS080601 inoculation. In addition, the maximum levels of free proline, soluble sugar, and protein in calli treated with LXS081501 plus LXS080601 were 2.14 to 3.47 times higher than controls and 1.42 to 1.75 times higher than LXS080601 treatment. The activities of defense-related enzymes such as phenylalanine ammonia lyase (PAL), polyphenol oxidase (PPO), peroxidase (POD), and catalase (CAT) as well as β-1,3-glucanase and chitinase in apple calli inoculated with LXS080601 alone or LXS081501 plus LXS080601 increased significantly 24 hai and peaked from 48 to 120 hpi. However, in the latter treatment, the maximum enzyme activities were much higher and the activities always maintained much higher levels than control during the experimental period. These results suggested the roles of osmotic adjustment substances and defense-related enzymes in induced resistance.